Biomechanical Analysis of Differential Pull-Out Strengths of Bone Screws Using Cervical Anterior Transpedicular Technique in Normal and Osteoporotic Cervical Cadaveric Spines. Issue 1 (1st January 2015) - Wu, Changfu; Chen, Chun; Wu, Weidong; Zhao, Weidong; Sun, Peidong; Fan, Jihong; Bi, Zhenyu; Zhang, Jinyuan; Ouyang, Jun
<x xml:space="preserve">Abstract</x> Study Design. Biomechanical in vitro study. Objective. To determine whether the peak pull-out force (PPF) of cervical anterior transpedicular screw (ATPS) fixed in osteoporotic vertebrae positively influence screw stability or not before and after fatigue. Summary of Background Data. Multilevel cervical spine procedures with osteoporosis can challenge the stability of current screw-and-plate systems. A second surgical posterior approach is coupled with potential risks of increased morbidity and complications. Hence, anterior cervical instrumentation that increases primary construct stability, while avoiding the need for posterior augmentation, would be valuable. Methods. Sixty formalin-fixed vertebrae at different levels were randomly selected. The vertebrae were divided into healthy controls (groups A1, A2), osteoporotic controls (B1, B2), healthy ATPS groups (C1, C2), osteoporotic ATPS groups (D1, D2), and osteoporotic restoration controls (E1, E2). The procedure of ATPS insertion was simulated with 2 pilot holes being drilled on each side of 20 vertebral bodies that were implanted with either vertebral screw or polymethylmethacrylate. Each side randomly received either instant PPF or PPF beyond fatigue (2.5 Hz; 20, 000 times). Results. The prefatigue PPFs were significantly higher than the postfatigue PPFs in all groups (group A: 366.06 ± 58.78 vs. 248.93 ± 57.21 N; group B: 275.58 ± 23.18 vs. 142.79 ± 44.78 N; group C: 635.99 ± 185.28 vs. 542.57 ± 136.58 N; group D: 519.22 ± 122.12 vs. 393.16 ± 192.07 N, and group E: 431.78 ± 75.77 vs. 325.74 ± 95.10 N). The postfatigue PPFs were reduced by 32.00% (group A), 48.19% (group B), 14.69% (group C), 24.28% (group D), and 24.72% (group E). The acute and postfatigue PPFs of both control groups were significantly lower than that of ATPS groups (P < 0.05). The cyclic osteoporosis ATPS group achieved the same PPF compared with the vertebral restoration screw group. Conclusion. The findings of this study suggest that instant PPF and fatigue resistance capability of an ATPS fixation were significantly better than other control groups, especially in the osteoporotic vertebrae. Level of Evidence: N/A